Conflicts in the practice of Dentistry: the autonomy in question - Cláudia Helena Soares de Morais Freitas; Eraldo José de Aguiar Júnior (Faculdade de Medicina de Botucatu (Unesp), 2007)
The study aimed to arrive at an understanding of the dynamics and the changes faced by dentistry, using the professional autonomy category and its significance to professional discourse and the strategies that are used to preserve professional autonomy. The reflections are based on the sociology of professions, particularly the concepts of autonomy, expertise and service ideal. The research revealed that professional autonomy is still a strong element with an important role to play in shaping the identity of the group and that autonomy has not been affected in spite of changes in the labor market.